Romania : Fifth Review Under the Stand-By Arrangement, and Requests for Waiver of Nonobservance of Performance Criterion, and Request for Modification and Establishment of Performance Criteria; Staff Report; Supplementary Information; Press Release on the Executive Board Discussion; Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2010)
Economic growth finally turned positive, but further recovery will be delayed, as fiscal austerity measures and recent floods will weigh on domestic demand. The macroeconomic outlook has weakened and continues to be subject to exceptional uncertainties. With the enactment of the ambitious adjustment package, fiscal policies are on track to meet the targets. Structural reforms continue to be geared toward supporting the fiscal consolidation agenda, and remain on track. The authorities have initiated a new reform of social assistance programs.